PKM PENTINGNYA PENGUASAAN SOFT SKILL BAGI GENERASI Z DI KALANGAN SISWA-SISWI SMA INTI NUSANTARA TEBING TINGGI - Dina Hastalona; Atma Jonar Asih; Ulpah Ulpah; Ridwan Ridwan; Mellyoni Mellyoni (Indonesian Collaboration Journal of Community Services, 2021)
The purpose of this Community Service (PKM) program is to provide knowledge and skills regarding soft skills to the students of SMA Inti Nusantara Tebing Tinggi. The specific target is to provide knowledge and skills to students in improving their skills through guidance in improving soft skills. The prospect of increasing soft skills aims to train personality, communication skills or personal attributes that are needed to be able to provide good performance in a job or business. The soft skills possessed will make it easy for these students to interact with the environment they enter. This community service program activity is to disseminate information to SMA Inti Nusantara students as Z generation, provide guidance or counseling that can improve soft skills skills through many activities that support it. This is done as an effort to improve soft skills for Z Generation  in order to face the era of the industrial revolution 4.0 and the era of society 5.0